Results of the treatment of median and ulnar nerves tunnel neuropathies - Tsymbaliuk, V. I.; Tretiak, I. B.; Tsymbaliuk, J. V. (Ukrainian Neurosurgical Journal)
We analyzed 65 patients with tunnel neuropathies (TN) who were operated on in the department of rehabilitation nerosurgery from 1994 to 2003. Age of patients — from 13 to75 years old, males — 73%, females — 27%. Distribution of lesion location was following: cubital channel 46, carpal channel-11, in6 cases both levels were involved. Surgical interventions include neurolisis and decompression of nerve trunks and theirs branches with insertion of stimulating electrode if needed. In the majority cases management of median nerve compression in carpal channel comprises in dissection of its anterior wall — carpal ligament. That resulting in enlargement of space in carpal channel ant to decrease on intrachannel pressure. Our results indicating necessity of early decompression and neurolisis for better nerve regeneration. The best timing for surgical intervention is the period from 1 to 6 months after onset of clinical symptoms.